La Société des Américanistes de Paris : une société savante au service de l’américanisme - Christine Laurière (Journal de la Société des Américanistes)
The Paris’ Society of Americanists: a learned society dedicated to Americanism. This article deals with the creation in 1895 of the Society of Americanists, the first one of its kind, and gives some reference points to understand its history. In the first part, it refers to the conditions of its creation by Ernest Théodore Hamy and its development under his guidance. In the second part, it discusses Paul Rivet’s strong commitment in the destiny of the Society and shows how he decidedly helped to expand its international influence. As an international leader of French Americanism during the first half of the twentieth century, he boosted its Journal that was worldwide unequalled for several decades. In the third part, this essay sketches out the main geographical, disciplinary and subject trends of the articles published in the Journal.